Neuroimmunology of Human T-Lymphotropic Virus Type 1-Associated Myelopathy/Tropical Spastic Paraparesis - Nozuma, Satoshi; Jacobson, Steven (Frontiers in Microbiology, 2019)
Human T-lymphotropic virus type 1 (HTLV-1) is the etiologic agent of both adult T-cell leukemia/lymphoma and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). HAM/TSP is clinically characterized by chronic progressive spastic paraparesis, urinary incontinence and mild sensory disturbance. Given its well characterized clinical presentation and pathophysiology which is similar to the progressive forms of multiple sclerosis (MS), HAM/TSP is an ideal system to better understand other neuroimmunological disorders such as MS. Since the discovery of HAM/TSP, large numbers of clinical, virological, molecular, and immunological studies have been published. The host-virus interaction and host immune response play an important role for the development with HAM/TSP. HTLV-1-infected circulating T-cells invade the central nervous system (CNS) and cause an immunopathogenic response against virus and possibly components of the CNS. Neural damage and subsequent degeneration can cause severe disability in patients with HAM/TSP. Little progress has been made in the discovery of objective biomarkers for grading stages and predicting progression of disease and the development of molecular targeted therapy based on the underlying pathological mechanisms. We review the recent understanding of immunopathological mechanism of HAM/TSP and discuss the unmet need for research on this disease.